Congo/Crimean haemorrhagic fever in Iraq - Al-Tikriti, S. K. (1981)
Congo/Crimean haemorrhagic fever was recognized for the first time in Iraq in 1979. The first case was reported on 3 September 1979 and since then a further 9 patients have been investigated. Eight patients gave a history of previous contact with sheep or cattle, while 2 patients, a resident doctor and an auxiliary nurse, acquired their infections in hospital by direct contact with patients. The causal virus was isolated from patients' blood and postmortem liver specimens. The virus isolates were found to be closely related if not identical serologically to members of the Congo/Crimean haemorrhagic fever virus group. Eight of the patients had no epidemiological relationship to one another and lived in widely separated areas around Baghdad and Ramadi (110 km to the west of Baghdad).